(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Creator has created this world in a very magnificent form. He has created his creation in various dimensions. An important dimension from these diverse dimensions is the effigy of the soil, by giving life to this inanimate effigy of the soil, it gave a living form, which gave the form of human being. In this living human effigy, the heart is a very sensitive and emotional sense. In this heart, many emotional elements like love, service, sacrifice, hatred, selfishness, etc. come up. The most grand and divine element among these emotional elements is ‘love’ the convention of other emotions that rise in the heart is contained in this love element.Love is the basis of man’s life, love makes the world at peace, not only this, society also helps to tie the country and the world brotherhood in one thread. From the ancient times till today, the sweet juice stream of love has been flowing continuously. This juice stream has gained an important place in the female-male relationship. Every person has consumed this sweet juice stream and is still doing it today. This ’two and a half’ love has elevated the heads of many people and restored them the title of superiority and has become a proud form of their reputation. In contrast, this ’two and a half’ love has become a blot of slander by trampling many people in the soil. Due to this dialectical situation, this emotional element has become the subject of deliberation. Love forms itself in many ways that we would like to see in a psychological context.